Isolation of fungi associated with coffee beans from producing areas in northern Santander, Colombia. (@limentech, Ciencia y Tecnología Alimentaria, 2016)
The coffee trade is one of the most important economic sectors worldwide; however, it is also susceptible to contamination from harvest to processing. For this study, coffee cherry samples were collected from different producing municipalities in Norte de Santander. The following fungal agents were subsequently isolated and phenotypically characterized from the coffee bean in the laboratory: Aspergillus spp., Penicillium spp., Fusarium spp., Cladosporium spp., Mucor spp., and Rhizopus spp. using taxonomic keys. The fungi with the highest incidence were Aspergillus spp. and Fusarium spp. Among the three physicochemical variables analyzed in the coffee cherry (pH, water activity, moisture content), it can be stated with certainty that water activity and moisture content directly influence the number and type of fungal isolates obtained
Keywords: Isolation; coffee; cherry; characterization; fungi